Modernisierung und Totalismus: Nationalsozialismus und Sowjetkommunismus in vergleichender Perspektive - Spohn, Willfried (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1999)
On the backdrop of the recent, however conflictual revival of theories of modernization and totalitarianism, this paper analyzes German National-Socialism as well as GDR- and Soviet-Russian Communism as two, but rather different types of totalitarian political orders. By using Shmuel Eisenstadt's concept of totalism as an inherent potentiality of modernity and modernization processes, I attempt at explaining the differences between both types of totalitarian regimes as specific configurations of modernization trajectories and their totalistic components in Germany and in Soviet Russia. This explanatory approach transcends the common opposition between theories of modernization and theories of totalitarianism by combining the two in a specific comparative historical-sociological approach.